Molecular characterization of plasmid-mediated non-O157 verotoxigenic escherichia coli isolated from infants and children with diarrhea - Karim Khan, Md Fazlul; Rashid, Shah Samiur; Mohammad, Nazmul; Hassan, Maziz; Aizi Nor Mazila, Ramli; Roesnita, Baharuddin (University of Baghdad, 2020)
A significant increase in the incidence of non-O157 verotoxigenic Escherichia coli (VTEC) infections have become a serious health issues, and this situation is worsening due to the dissemination of plasmid mediated multidrug-resistant microorganisms worldwide. This study aims to investigate the presence of plasmid-mediated verotoxin gene in non-O157 E. coli. Standard microbiological techniques identified a total of 137 E. coli isolates. The plasmid was detected by Perfectprep Plasmid Mini preparation kit. These isolates were subjected to disk diffusion assay, and plasmid curing with ethidium bromide treatment. The plasmid containing isolates were subjected to a polymerase chain reaction (PCR) for investigating the presence of plasmid mediated verotoxin gene (VT1 and VT2) in non-O157 E. coli. Among the 137 E. coli isolates, 49 isolates were non-O157 E. coli while 29 (59.1%) isolates were verotoxin producing non-O157 serotypes and 26 non-O157 VTEC isolates possessed plasmids. Certain isolates harboured single sized plasmid while others had multiple plasmids with different size varied from 1.8kb to 7.6kb. A plasmid containing all (100%) the isolates was multidrug-resistant. Eight isolates changed their susceptibility patterns while three isolates were found to lose plasmid after post plasmid curing treatment and the rest of the isolates (15) remained constant. Different PCR sets characterized 3 plasmid-mediated verotoxins producing non-O157 E. coli. This current study demonstrated the occurrence of plasmid mediated verotoxin gene in non-O157 E. coli. To the best of our knowledge, this is the first report in the global literature on plasmid-mediated verotoxin gene in non-O157 E. coli. Timely diagnosis and surveillance of VTEC infections should prioritize to stop or slow down the virulence gene for dissemination by plasmid-mediated gene transfer amongst the same bacteria or other species.